WORKSHOP UNTUK PEMUDA PUTUS SEKOLAH DI KELURAHAN LAMBUNG BUKIT KECAMATAN PAUH PADANG DALAM BIDANG PENGELASAN - Nota Effiandi; Mulyadi Mulyadi; Fardinal Fardinal; Bukhari Bukhari; Alfian Alfian; Nofriadi Nofriadi; Ichlas Nur; Yuli Yetri (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
SMAW 2F welding training has been carried out at the Politeknik Negeri Padang (PNP) for youth from the Lambung Bukit sub-district, Pauh sub-district, Padang city in order to carry out the Tri Dharma of Higher Education. The SMAW 2F welding workshop was supported by the head of the Community Empowerment Agency (BPM) and Kelurahan because the community had been waiting for this activity for a long time. High school graduates in Lambung Bukit sub-district who do not yet have adequate skills to be able to compete in filling employment opportunities. With current technological developments, especially in the field of information technology, Lambung Bukit sub-district has experienced extraordinary development, due to the assimilation between the natives and the newcomers. On the other hand, population growth must also be followed by an increase in living facilities. To harmonize the progress of the two fields with the capabilities of human resources, various training and skills are needed, one of which is skills training in the field of electric welding. SMAW 2F electric welding training is currently very much needed to fill the shortage of labor in the welding field. After it was agreed with Kelurahan the PNP service team held a 4-day training which was attended by 30 Lambung Bukit youths at the Padang State Polytechnic Mechanical Engineering workshop. The results obtained showed that Lambung Bukit youth were able to perform SMAW electric welding using the 2F method well according to recognized welding standards. With the results obtained, all training participants received a SMAW 2F welding certificate from the Politeknik Negeri Padang. The Lambung Bukit community hopes that this kind of training can be carried out continuously because many young people want to improve their competencies which can be a provision in opening entrepreneurship and filing available job opportunities.